The Fear of Me: Representation and Reflection of Quarter Life Crisis in the Song 'Takut' by Idgitaf - Nadina Ramadhany; Fitri Argarini (I-Pop: International Journal of Indonesian Popular Culture and Communication, 2022)
The quarter-life crisis is an issue that is being discussed because it relates to the anxiety and worries of someone aged 18-29. One song that raises the issue of the quarter-life crisis is "Takut" (Fear) by Idgitaf. The song reflects the form of worry when entering your 20s. This study aims to determine the representation of the quarter-life crisis in the lyrics of the song "Takut" by Idgitaf. The research method used in this research is the semiotic analysis method of Roland Barthes, and the data collection techniques used are textual observation and document search. The results indicate that the song "Takut" represents the quarter-life crisis which is indicated by the phases and factors that cause the quarter-life crisis. Based on the findings, the song "Takut" has meaning of anxiety. It is when entering adulthood can subside if a person knows how to deal with things that cause instability, such as self-discovery, lifestyle changes, to pressure from the surrounding environment.